Automated Security Management - Al-Shaer, Ehab.; Ou, Xinming; Xie, Geoffrey; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
No back cover copy.
1: Towards a Unified Modeling and Verification of Network and System Security Configurations -- 2: Modeling and Checking the Security of DIFC System Configurations -- 3: Increasing Android Security using a Lightweight OVAL-based Vulnerability Assessment Framework -- 4: A Declarative Logic-based Approach for Threat Analysis of Advanced Metering Infrastructure -- 5: Risk based Access Control using Classification -- 6: GCNav - Generic Configuration Navigation System -- 7: The Right Files at the Right Time -- 8: Rule Configuration Checking in Secure Cooperative Data Access -- 9: Programmable Diagnostic Network Measurement with Localization and Traffic Observation -- 10: Discovery of Unexpected Services and Communication Paths in Networked Systems -- 11: Tracing Advances Persistent Threats in Networked Systems.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer Science; Systems and Data Security; Data Encryption; Computer Communication Networks